Bending Characteristics of Foldable Touch Display Panel with a Protection Structure Design - Hsien-Chie Cheng; Wei-Heng Xu; Wen-Hwa Chen; Pi-Hsien Wang; Kuo-Feng Chen; Chih-Chia Chang (Advances in Materials Science and Engineering)
The study proposes and demonstrates an enhancement of a touch display panel (TDP) through a polymer-based protection structure to achieve higher bendability and reliability. The bending performance of the TDP without or with the protection structure designs is addressed using three-dimensional geometry-nonlinear finite element analysis and mechanical testing. The elastic properties of the components in the TDP structure are derived from nanoindentation and uniaxial tensile/compressive testing. The calculated results are compared with each other and also against the experimental bending fatigue test data. At last, a design guideline and optimal factor setting for enhanced bending performance are sought through parametric FE analysis and Taguchi experimental design, respectively. The optimal design is compared with the original in terms of bending stress. The simulation results show that bending would create significant tensile and compressive bending stresses on the indium tin oxide/dielectric layers, which are the main cause of several commonly observed failures, such as thin film cracking and delamination, in a thin rigid film coating on a thick compliant substrate. It also turns out that a substrate with a lower stiffness has a better mechanical stability against bending stress.